Successful factors for innovation and their impact on performance of Malaysian small and medium entreprises - Mah, Wai Lan (2018)
Innovation among small and medium enterprises (SMEs) has been the popular research topic of many researchers in the past decades due to its significant contribution to economic growth. However, according to the OECD Review of Innovation Policy in 2011, Malaysia has yet to enter a stage of innovation-led growth in the last decade. This phenomenon suggests that some practical gaps should be filled, where sources that improve innovativeness of SMEs should be examined in order to successfully promote innovation-led growth amongst SMEs in Malaysia. Using Resource-Based View (RBV) as underpinning theory, this study examines the relationship between sources of innovation, innovation and firm performance in the context of manufacturing and service sector of Malaysia SMEs. A total of 125 samples were used in data analysis using partial least squares (PLS) techniques for hypothesis testing. The findings of the hypothesis testing showed that R&D strategy, strategic relationship and customer relationship have positive impact on innovation where strategic leadership was the most influencing source of innovation. Meanwhile, government support and supplier also have indirectly impact on innovation through the mediating effect of R&D strategy. The findings also showed that innovation significantly contributed to firm performance, at the same time it plays vital mediator role in the model. It is concluded that all the sources in the framework are important contributors to innovation and firm performance except learning orientation.